Anti-radiation polyether ether ketone polymer material and preparation process thereof

CN122978682APending Publication Date: 2026-10-27ANHUI ZHUOREN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611378627.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但纯聚醚醚酮高分子本身抗辐射能力有限,在长期电磁、电离辐射环境下,高分子链易受辐射诱导产生自由基,引发分子链断链、交联老化,造成材料力学性能衰减;同时纯PEEK本身几乎不具备电磁波吸收屏蔽能力,难以满足辐射工况下的防护使用需求

Benefits of technology

(1)本发明中,采用聚醚砜对碳纳米管进行接枝改性,聚醚砜链段包覆于碳纳米管表面,有效削弱碳纳米管间范德华力、缓解团聚缠绕问题,提升其在PEEK基体中的分散性与界面相容性,能够构建连续高效的导电网络;同时引入石墨-铁钴磁性粒子复合电磁波吸收材料,石墨提供电导损耗、铁钴磁性粒子提供磁损耗,二者协同作用拓宽电磁波吸收频段,在保障材料延展性的前提下,显著提升材料的电磁辐射屏蔽效能,实现高效抗辐射防护。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978682A_ABST
    Figure CN122978682A_ABST
Patent Text Reader

Abstract

The application discloses an anti-radiation polyether ether ketone polymer material and a preparation process thereof, and relates to the technical field of polyether ether ketone polymer materials, and comprises the following components in parts by mass: fluorine-terminated modified PEEK resin 70-90 parts, polyether sulfone modified carbon nanotube 3-12 parts, composite electromagnetic wave absorbing material 5-18 parts, hyperbranched polyester self-healing agent 0.2-1.5 parts, and composite stabilizing aid 0.5-3 parts. In the application, the polyether sulfone is used to graft modify the carbon nanotube, the polyether sulfone chain segment is coated on the surface of the carbon nanotube, the van der Waals force between the carbon nanotubes is effectively weakened, the agglomeration and winding problems are relieved, the dispersibility and the interfacial compatibility of the carbon nanotube in the PEEK matrix are improved, and a continuous and efficient conductive network can be constructed; meanwhile, the graphite-iron cobalt magnetic particle composite electromagnetic wave absorbing material is introduced, the graphite provides electric conduction loss, the iron cobalt magnetic particle provides magnetic loss, and the two synergistically broaden the electromagnetic wave absorption frequency band, so that the electromagnetic radiation shielding efficiency of the material is significantly improved under the premise of guaranteeing the ductility of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyetheretherketone (PEEK) polymer materials technology, specifically to a radiation-resistant PEEK polymer material and its preparation process. Background Technology

[0002] Polyetheretherketone (PEEK), as a high-performance specialty engineering plastic, possesses outstanding mechanical strength, resistance to high and low temperatures, chemical corrosion resistance, and dimensional stability, making it a promising candidate for applications in radiation-exposed environments such as aerospace, nuclear industry, and electronic devices. However, pure PEEK polymers themselves have limited radiation resistance. Under long-term electromagnetic and ionizing radiation environments, the polymer chains are susceptible to radiation-induced free radical generation, leading to chain breakage, cross-linking aging, and a decline in the material's mechanical properties. Furthermore, pure PEEK itself has almost no electromagnetic wave absorption or shielding capabilities, making it difficult to meet the protective requirements under radiation conditions.

[0003] In existing technologies, conductive fillers such as carbon nanotubes and graphite are usually added directly to the PEEK matrix to improve electromagnetic shielding performance. However, carbon nanotubes have a large specific surface area and strong intermolecular van der Waals forces, making them prone to agglomeration and entanglement when directly blended. The filler has poor interfacial compatibility with the PEEK matrix, which not only makes it difficult to construct a continuous and efficient conductive loss network, but also reduces the material's ductility and increases mechanical defects. In addition, single carbon-based fillers are mainly responsible for electrical conduction loss and have insufficient magnetic loss capacity, resulting in a limited electromagnetic wave absorption bandwidth and poor overall radiation resistance.

[0004] To address these issues, this invention proposes a radiation-resistant polyether ether ketone polymer material and its preparation process. Summary of the Invention (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a radiation-resistant polyether ether ketone polymer material and its preparation process, thus solving the problems mentioned in the background section.

[0005] (II) Technical Solution To achieve the above objectives, the present invention is implemented through the following technical solution: a radiation-resistant polyether ether ketone polymer material, comprising, by weight: 70-90 parts of fluorine-terminated modified PEEK resin, 3-12 parts of polyether sulfone-modified carbon nanotubes, 5-18 parts of composite electromagnetic wave absorbing material, 0.2-1.5 parts of hyperbranched polyester self-healing agent, and 0.5-3 parts of composite stabilizing agent; The polyethersulfone modified carbon nanotubes are prepared by amidation grafting of carbon nanotubes treated with mixed acid oxidation with aminated polyethersulfone. The composite electromagnetic wave absorbing material is prepared by ultrasonic dispersion and composite of graphite and iron-cobalt magnetic particles. The fluorinated end-modified PEEK resin is a modified polyether ether ketone with 4,4-dichlorobenzophenone and hydroquinone as monomers and fluoride end-capping agent for end-group passivation. The iron-cobalt magnetic particles are composed of Prepared via hydrothermal reaction.

[0006] Preferably, the mass of the raw material for preparing iron-cobalt magnetic particles is [missing information]. , 7.5 parts hydrazine hydrate, 7.5 parts sodium hydroxide; The specific preparation method is as follows: [The following is a more detailed preparation method:] Dissolve sodium hydroxide in distilled water with magnetic stirring; dissolve sodium hydroxide in a mixture of hydrazine hydrate and distilled water; transfer both solutions to a hydrothermal reactor and react at 78°C for 4 hours; separate the product with a magnet, wash with water until neutral, and vacuum dry at 75-85°C for 3.5-4.5 hours.

[0007] Preferably, the composite electromagnetic wave absorbing material contains the following raw material mass parts: 7.5-8.5 parts graphite and 1.5-2.5 parts iron-cobalt magnetic particles; during preparation, the graphite and iron-cobalt magnetic particles are ultrasonically dispersed in ethanol for 0.8-1.2 hours, mixed evenly, and then dried.

[0008] Preferably, the mixed acid oxidation treatment of carbon nanotubes involves mixing multi-walled carbon nanotubes with a nitric acid-sulfuric acid mixture at a volume ratio of 1:3, reacting at a temperature of 75-85°C, stirring for 1.5-2.5 hours, sonicating for 0.8-1.2 hours, and centrifuging at a speed of 4500-5500 rpm.

[0009] Preferably, the preparation step of the aminated polyethersulfone includes: nitrifying polyethersulfone with a nitric acid-sulfuric acid mixture to obtain nitrated polyethersulfone, and then reducing it with a tin chloride-hydrochloric acid-ethanol system to obtain aminated polyethersulfone; the nitration reaction temperature is 55-65℃, the reaction time is 5-7h, and the reduction reaction temperature is 55-65℃, the reaction time is 3.5-4.5h.

[0010] Preferably, the polyethersulfone modified carbon nanotubes are prepared by reacting 0.4-0.6 parts of carbon nanotube oxide, 5-6 parts of amino-modified polyethersulfone, 18-22 parts of N,N'-dicyclohexylcarbodiimide, and 1.2-1.8 parts of dimethylaminopyridine in nitrogen protection in dehydrated N,N-dimethylformamide for 22-26 hours.

[0011] Preferably, the fluoride end-capping agent is 4-fluorobenzophenone or 4-tert-butyl-4'-fluorobenzophenone; the end-capping agent is added at the end of the polycondensation process, and the displacement reaction is carried out at a constant temperature for 2-3 hours.

[0012] Preferably, the hyperbranched polyester self-healing agent is a hydroxyl-terminated hyperbranched polyester, which is prepared by using trimethylolpropane as the core and 2,2-dimethylolpropionic acid as the monomer; wherein the molar ratio of trimethylolpropane to 2,2-dimethylolpropionic acid is 1:6-12.

[0013] Preferably, the composite stabilizing agent is a compound of hindered phenolic primary antioxidant, phosphite secondary antioxidant, and aromatic amine free radical scavenger; wherein the mass ratio of hindered phenolic primary antioxidant, phosphite secondary antioxidant, and aromatic amine free radical scavenger is 2-4∶1-2∶0.5-1.

[0014] A preparation process for a radiation-resistant polyetheretherketone polymer material includes the following steps: S1. Preparation of iron-cobalt magnetic particles; S2. Graphite and iron-cobalt magnetic particles are ultrasonically dispersed and composited in ethanol to prepare graphite / iron-cobalt composite electromagnetic wave absorbing material. S3. Multi-walled carbon nanotubes are subjected to mixed acid oxidation treatment to prepare oxidized carbon nanotubes; S4. Prepare amino-modified polyethersulfone and then graft it onto the surface of carbon oxide nanotubes to obtain polyethersulfone-modified carbon nanotubes. S5. Using 4,4-dichlorobenzophenone and hydroquinone as monomers, and fluoride end-capping agent, fluorine-terminated modified PEEK resin was synthesized. S6. Fluorine-terminated modified PEEK resin, hyperbranched polyester self-healing agent, composite stabilizer, polyethersulfone modified carbon nanotubes, and composite electromagnetic wave absorbing material are put into a high-speed internal mixer and melt-blended at low temperature and low speed to obtain radiation-resistant polyether ether ketone polymer material.

[0015] (III) Beneficial Effects This invention provides a radiation-resistant polyetheretherketone polymer material and its preparation process. Compared with the prior art, it has the following advantages: (1) In this invention, polyethersulfone is used to graft and modify carbon nanotubes. The polyethersulfone segments are coated on the surface of carbon nanotubes, which effectively weakens the van der Waals forces between carbon nanotubes, alleviates the problem of agglomeration and entanglement, and improves its dispersion and interfacial compatibility in the PEEK matrix, thus enabling the construction of a continuous and efficient conductive network. At the same time, a graphite-iron-cobalt magnetic particle composite electromagnetic wave absorbing material is introduced. Graphite provides electrical conductivity loss and iron-cobalt magnetic particles provide magnetic loss. The two work together to broaden the electromagnetic wave absorption frequency band. Under the premise of ensuring the material's ductility, the electromagnetic radiation shielding performance of the material is significantly improved, thus achieving efficient anti-radiation protection.

[0016] (2) In this invention, fluoride is used to seal and passivate the active end groups of PEEK molecular chains to suppress the polymer chain degradation reaction caused by active end groups under radiation and thermal environment; the formulation is composed of a composite stabilizer consisting of hindered phenolic main antioxidant, phosphite auxiliary antioxidant and aromatic amine free radical scavenger, which can synergistically capture free radicals generated by radiation, decompose peroxides and inhibit oxidative degradation; at the same time, a terminal hydroxyl hyperbranched polyester self-healing agent is introduced, which can achieve self-repair by means of molecular chain fluidity when the material is damaged, and reduce the accumulation of internal defects; the three work together to greatly improve the mechanical property retention rate and service life of the material under thermal-radiation coupling environment. Attached Figure Description

[0017] Figure 1 Transmission electron microscopy (TEM) images of untreated carbon nanotubes and polyethersulfone-modified carbon nanotubes provided by this invention. Detailed Implementation

[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] Preparation of hydroxyl-terminated hyperbranched polyester: Trimethylolpropane and 2,2-dimethylolpropionic acid in a molar ratio of 1:9 were added to a reactor, and 0.4% by mass of p-toluenesulfonic acid was added as an esterification catalyst; under nitrogen protection, the temperature was raised to 140℃ for melt esterification, and water generated by the reaction was removed; the temperature was gradually raised to 170℃, and dehydration was continued under reduced pressure and vacuum for 5 hours. After cooling, the product was discharged to obtain hydroxyl-terminated hyperbranched polyester.

[0020] Preparation of composite stabilizer: Pentaerythritol tetrakis[-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (hindered phenolic primary antioxidant), tris(2,4-di-tert-butylphenyl) phosphite (phosphite secondary antioxidant), and N-phenyl-naphthylamine (aromatic amine free radical scavenger) were mixed evenly in a mass ratio of 3:1.5:0.8 to obtain the composite stabilizer.

[0021] Preparation of fluorine-terminated modified PEEK resin: Under nitrogen protection, nucleophilic polycondensation reaction was carried out using 4,4-dichlorobenzophenone and hydroquinone as monomers. At the end of the polycondensation reaction, 4-fluorobenzophenone was added as a fluoride end-capping agent, and the reaction was carried out at a constant temperature for 2.5 h to obtain fluorine-terminated modified PEEK resin.

[0022] Preparation of cobalt-iron magnetic particles: Take Dissolve in 60 mL of distilled water and stir magnetically until fully dissolved; dissolve 7.5 parts of sodium hydroxide in a mixed solution of 7.5 parts of hydrazine hydrate and 10 mL of distilled water; transfer the two solutions to a hydrothermal reactor and react hydrothermally at 78 °C for 4 h; separate the solid product using a magnet, wash with distilled water until the pH of the filtrate is neutral, and dry in a vacuum oven at 80 °C for 4 h to obtain iron-cobalt magnetic particles.

[0023] Preparation of composite electromagnetic wave absorbing material: Take 8.0 parts of graphite and 2.0 parts of the iron-cobalt magnetic particles prepared above, add them to 200 mL of anhydrous ethanol, ultrasonically disperse for 1 h, after the mixture is fully homogeneous, remove the solvent and dry to obtain graphite-iron-cobalt magnetic particle composite electromagnetic wave absorbing material.

[0024] Preparation of mixed acid oxidized carbon nanotubes: 1 part of multi-walled carbon nanotubes was added to a nitric acid-sulfuric acid mixed acid system with a volume ratio of 1:3, stirred at 80℃ for 2 hours, and then sonicated for 1 hour; centrifuged at 5000 rpm, the solid was collected, and repeatedly filtered and washed with deionized water until the filtrate was neutral, and dried at 100℃ to obtain mixed acid oxidized carbon nanotubes.

[0025] The preparation of aminated polyethersulfone: 10g of polyethersulfone micro powder was added to a nitric acid-sulfuric acid mixture with a volume ratio of 3:4 and nitrated at 60℃ for 6h; cooled, filtered, washed with water, and dried at 80℃ to obtain nitrated polyethersulfone; 3g of nitrated polyethersulfone was added to a tin chloride-hydrochloric acid-ethanol reduction system and reduced at 60℃ for 4h; filtered, washed with water, and dried at 100℃ to obtain aminated polyethersulfone.

[0026] Preparation of polyethersulfone modified carbon nanotubes: 0.5 parts of carbon nanotube oxide were dispersed in dehydrated N,N-dimethylformamide and sonicated for 30 min to obtain a carbon nanotube suspension; 5.5 parts of aminated polyethersulfone, 20 parts of N,N'-dicyclohexylcarbodiimide, and 1.5 parts of dimethylaminopyridine were dissolved in dehydrated N,N-dimethylformamide and stirred to dissolve; the two liquid phases were mixed and stirred under nitrogen protection for 24 h; the solid was filtered, thoroughly washed, and vacuum dried at 80 °C for 24 h to obtain polyethersulfone modified carbon nanotubes.

[0027] Example 1 A radiation-resistant polyether ether ketone polymer material, by weight, comprises: 85 parts of fluorine-terminated modified PEEK resin, 6 parts of polyether sulfone-modified carbon nanotubes, 8 parts of composite electromagnetic wave absorbing material, 0.6 parts of hydroxyl-terminated hyperbranched polyester self-healing agent, and 1.2 parts of composite stabilizing agent.

[0028] Preparation process: The fluorine-terminated modified PEEK resin, polyethersulfone modified carbon nanotubes, composite electromagnetic wave absorbing material, hydroxyl-terminated hyperbranched polyester self-healing agent and composite stabilizing agent in the above proportions are put into the high-speed internal mixer. The internal mixer barrel temperature is set to 350℃ and the rotor speed is 80r / min. Low temperature and low speed conditions are used for melt blending. The blending time is 10min. After blending, the material is discharged and granulated to obtain radiation-resistant polyether ether ketone polymer material.

[0029] Example 2 A radiation-resistant polyether ether ketone polymer material, by weight, comprises: 80 parts of fluorine-terminated modified PEEK resin, 8 parts of polyether sulfone-modified carbon nanotubes, 12 parts of composite electromagnetic wave absorbing material, 1.0 part of hydroxyl-terminated hyperbranched polyester self-healing agent, and 2.0 parts of composite stabilizing agent.

[0030] Preparation process: The fluorine-terminated modified PEEK resin, polyethersulfone modified carbon nanotubes, composite electromagnetic wave absorbing material, hydroxyl-terminated hyperbranched polyester self-healing agent and composite stabilizing agent in the above proportions are put into the high-speed internal mixer. The internal mixer barrel temperature is set to 350℃ and the rotor speed is 80r / min. Low temperature and low speed conditions are used for melt blending. The blending time is 10min. After blending, the material is discharged and granulated to obtain radiation-resistant polyether ether ketone polymer material.

[0031] Example 3 A radiation-resistant polyether ether ketone polymer material, by weight, comprises: 75 parts of fluorine-terminated modified PEEK resin, 10 parts of polyether sulfone-modified carbon nanotubes, 16 parts of composite electromagnetic wave absorbing material, 1.4 parts of hydroxyl-terminated hyperbranched polyester self-healing agent, and 2.8 parts of composite stabilizing agent.

[0032] Preparation process: The fluorine-terminated modified PEEK resin, polyethersulfone modified carbon nanotubes, composite electromagnetic wave absorbing material, hydroxyl-terminated hyperbranched polyester self-healing agent and composite stabilizing agent in the above proportions are put into the high-speed internal mixer. The internal mixer barrel temperature is set to 350℃ and the rotor speed is 80r / min. Low temperature and low speed conditions are used for melt blending. The blending time is 10min. After blending, the material is discharged and granulated to obtain radiation-resistant polyether ether ketone polymer material.

[0033] Comparative Example 1 The difference from Example 1 is that ordinary unmodified multi-walled carbon nanotubes are used instead of polyethersulfone modified carbon nanotubes. By weight, the components are: 85 parts of fluorine-terminated modified PEEK resin, 6 parts of unmodified multi-walled carbon nanotubes, 8 parts of composite electromagnetic wave absorbing material, 0.6 parts of hydroxyl-terminated hyperbranched polyester self-healing agent, and 1.2 parts of composite stabilizing agent.

[0034] The preparation process is the same as in Example 1.

[0035] Comparative Example 2 The difference from Example 1 is that no composite electromagnetic wave absorbing material is added to the formulation. By weight, the components are: 85 parts of fluorine-terminated modified PEEK resin, 6 parts of polyethersulfone modified carbon nanotubes, 0.6 parts of hydroxyl-terminated hyperbranched polyester self-healing agent, and 1.2 parts of composite stabilizing agent.

[0036] The preparation process is the same as in Example 1. Comparative Example 3 The difference from Example 1 is that ordinary uncapped PEEK resin is used instead of fluorine-capped modified PEEK resin. By weight, the components are: 85 parts ordinary uncapped PEEK resin, 6 parts polyethersulfone modified carbon nanotubes, 8 parts composite electromagnetic wave absorbing material, 0.6 parts hydroxyl-terminated hyperbranched polyester self-healing agent, and 1.2 parts composite stabilizing agent.

[0037] The preparation process is the same as in Example 1.

[0038] Comparative Example 4 The difference from Example 1 is that no hyperbranched polyester self-healing agent is added to the formulation. By weight, the components are: 85 parts of fluorine-terminated modified PEEK resin, 6 parts of polyethersulfone modified carbon nanotubes, 8 parts of composite electromagnetic wave absorbing material, and 1.2 parts of composite stabilizing agent.

[0039] The preparation process is the same as in Example 1.

[0040] Comparative Example 5 The difference from Example 1 is that no composite stabilizing agent is added to the formulation. By weight, the components are: 85 parts of fluorine-terminated modified PEEK resin, 6 parts of polyethersulfone modified carbon nanotubes, 8 parts of composite electromagnetic wave absorbing material, and 0.6 parts of hydroxyl-terminated hyperbranched polyester self-healing agent.

[0041] The preparation process is the same as in Example 1.

[0042] Performance testing: Sample size: 150mm x 150mm x 2mm.

[0043] Ductility test: Tensile tests were conducted using a universal testing machine with a tensile rate of 5 mm / min. The elongation at break of the specimen was used to characterize the ductility of the material. Five specimens were tested for each sample, and the arithmetic mean was taken. The results are shown in Table 1.

[0044] Electromagnetic radiation shielding effectiveness test: A vector network analyzer was used, and the test frequency range was 1-18 GHz, according to the ASTM D4935-10 standard for testing electromagnetic shielding effectiveness of planar materials. The results are shown in Table 1.

[0045] Tensile strength retention test after heat aging: The samples were placed in a hot air aging chamber, and the aging temperature was set to 180-202°C for 200 hours. The samples were then removed and cooled to room temperature in a desiccator. The tensile strength of the samples before and after aging was tested respectively. Five samples were tested in parallel for each group, and the arithmetic mean was taken; the results are shown in Table 1.

[0046] Table 1 ductility Electromagnetic radiation shielding effectiveness / dB Tensile strength retention rate after heat aging / % Example 1 82 42.6 91.3 Example 2 80 45.1 89.7 Example 3 78 47.5 87.2 Comparative Example 1 61 31.2 76.5 Comparative Example 2 65 18.4 84.1 Comparative Example 3 70 38.3 72.6 Comparative Example 4 73 41.8 83.5 Comparative Example 5 76 42.1 60.4 Combining the test data in Table 1 and Figure 1 Analysis of transmission electron microscopy images shows that: Figure 1 In the middle (a), there are unmodified carbon nanotubes with a large number of carbon nanotubes entangled and aggregated together; Figure 1 (b) The polyethersulfone modified carbon nanotubes of the present invention have a polymer layer coated on the surface of the carbon nanotubes, which significantly reduces the aggregation phenomenon and greatly improves the dispersibility of the filler in the PEEK matrix.

[0047] Comparative Example 1 used unmodified carbon nanotubes, which resulted in severe agglomeration of the carbon nanotubes. The filler had poor compatibility with the matrix, and the material's ductility, electromagnetic shielding effectiveness, and thermal aging performance all decreased significantly.

[0048] Comparative Example 2 did not add composite electromagnetic wave absorbing material, and the system lacked electromagnetic loss components, resulting in a significant decrease in electromagnetic radiation shielding effectiveness.

[0049] Comparative Example 3 uses ordinary uncapped PEEK resin. The active end groups of the molecular chain are not passivated, and molecular chain degradation is likely to occur during the heat aging process. The tensile strength retention rate is significantly reduced after heat aging.

[0050] Comparative Example 4, without the addition of hyperbranched polyester self-healing agent, resulted in the material losing its self-healing function and exhibiting a reduction in mechanical properties.

[0051] Comparative Example 5, without the addition of composite stabilizing agents, is prone to free radical oxidative degradation under thermal aging conditions, and the tensile strength retention rate decreases significantly after thermal aging.

[0052] Furthermore, any content not described in detail in this specification is existing technology known to those skilled in the art.

[0053] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "include," "contain," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus.

[0054] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A radiation-resistant polyetheretherketone polymer material, characterized in that, By weight, it includes: 70-90 parts of fluorine-terminated modified PEEK resin, 3-12 parts of polyethersulfone modified carbon nanotubes, 5-18 parts of composite electromagnetic wave absorbing material, 0.2-1.5 parts of hyperbranched polyester self-healing agent, and 0.5-3 parts of composite stabilizing agent. The polyethersulfone modified carbon nanotubes are prepared by amidation grafting of carbon nanotubes treated with mixed acid oxidation with aminated polyethersulfone. The composite electromagnetic wave absorbing material is prepared by ultrasonic dispersion and composite of graphite and iron-cobalt magnetic particles. The fluorinated end-modified PEEK resin is a modified polyether ether ketone with 4,4-dichlorobenzophenone and hydroquinone as monomers and fluoride end-capping agent for end-group passivation. The iron-cobalt magnetic particles are composed of Prepared via hydrothermal reaction.

2. The radiation-resistant polyetheretherketone polymer material according to claim 1, characterized in that: The mass of the raw materials for preparing the iron-cobalt magnetic particles is [missing information]. , 7.5 parts hydrazine hydrate, 7.5 parts sodium hydroxide; The specific preparation method is as follows: [The following is a more detailed preparation method:] Dissolve sodium hydroxide in distilled water with magnetic stirring; dissolve sodium hydroxide in a mixture of hydrazine hydrate and distilled water; transfer both solutions into a hydrothermal reactor and react at 78°C for 4 hours. The product was separated by magnetization, washed with water until neutral, and vacuum dried at 75-85℃ for 3.5-4.5 hours.

3. The radiation-resistant polyetheretherketone polymer material according to claim 1, characterized in that: The composite electromagnetic wave absorbing material contains the following raw material weights: 7.5-8.5 parts graphite and 1.5-2.5 parts iron-cobalt magnetic particles. During preparation, the graphite and iron-cobalt magnetic particles are ultrasonically dispersed in ethanol for 0.8-1.2 hours, mixed evenly, and then dried.

4. The radiation-resistant polyetheretherketone polymer material according to claim 1, characterized in that: The mixed acid oxidation treatment of carbon nanotubes involves mixing multi-walled carbon nanotubes with a nitric acid-sulfuric acid mixture at a volume ratio of 1:3, reacting at 75-85℃, stirring for 1.5-2.5 hours, sonicating for 0.8-1.2 hours, and centrifuging at 4500-5500 rpm.

5. The radiation-resistant polyetheretherketone polymer material according to claim 1, characterized in that: The preparation steps of the aminated polyethersulfone include: nitrifying polyethersulfone with a nitric acid-sulfuric acid mixture to obtain nitrated polyethersulfone, and then reducing it with a tin chloride-hydrochloric acid-ethanol system to obtain aminated polyethersulfone; the nitration reaction temperature is 55-65℃, the reaction time is 5-7h, and the reduction reaction temperature is 55-65℃, the reaction time is 3.5-4.5h.

6. The radiation-resistant polyetheretherketone polymer material according to claim 1, characterized in that: The polyethersulfone-modified carbon nanotubes were prepared by reacting 0.4-0.6 parts of oxidized carbon nanotubes, 5-6 parts of amino-modified polyethersulfone, 18-22 parts of N,N'-dicyclohexylcarbodiimide, and 1.2-1.8 parts of dimethylaminopyridine in nitrogen-protected dehydrated N,N-dimethylformamide for 22-26 hours.

7. The radiation-resistant polyetheretherketone polymer material according to claim 1, characterized in that: The fluoride end-capping agent is 4-fluorobenzophenone or 4-tert-butyl-4'-fluorobenzophenone; the end-capping agent is added at the end of the polycondensation period, and the replacement reaction is carried out at a constant temperature for 2-3 hours.

8. The radiation-resistant polyetheretherketone polymer material according to claim 1, characterized in that: The hyperbranched polyester self-healing agent is a hydroxyl-terminated hyperbranched polyester, which is prepared by using trimethylolpropane as the core and 2,2-dimethylolpropionic acid as the monomer; wherein the molar ratio of trimethylolpropane to 2,2-dimethylolpropionic acid is 1:6-12.

9. The radiation-resistant polyetheretherketone polymer material according to claim 1, characterized in that: The composite stabilizing agent is a compound of hindered phenolic primary antioxidant, phosphite secondary antioxidant, and aromatic amine free radical scavenger; wherein the mass ratio of hindered phenolic primary antioxidant, phosphite secondary antioxidant, and aromatic amine free radical scavenger is 2-4∶1-2∶0.5-1.

10. A preparation process for the radiation-resistant polyetheretherketone polymer material according to any one of claims 1-9, characterized in that, Includes the following steps: S1. Preparation of iron-cobalt magnetic particles; S2. Graphite and iron-cobalt magnetic particles are ultrasonically dispersed and composited in ethanol to prepare graphite / iron-cobalt composite electromagnetic wave absorbing material. S3. Multi-walled carbon nanotubes are subjected to mixed acid oxidation treatment to prepare oxidized carbon nanotubes; S4. Prepare amino-modified polyethersulfone and then graft it onto the surface of carbon oxide nanotubes to obtain polyethersulfone-modified carbon nanotubes. S5. Using 4,4-dichlorobenzophenone and hydroquinone as monomers, and fluoride end-capping agent, fluorine-terminated modified PEEK resin was synthesized. S6. Fluorine-terminated modified PEEK resin, hyperbranched polyester self-healing agent, composite stabilizer, polyethersulfone modified carbon nanotubes, and composite electromagnetic wave absorbing material are put into a high-speed internal mixer and melt-blended at low temperature and low speed to obtain radiation-resistant polyether ether ketone polymer material.